Adenocarcinoma of the Sinonasal Tract: A Review of the National Cancer Database - Patel, Neil N.; Maina, Ivy W.; Kuan, Edward C.; Triantafillou, Vasiliki; Trope, Michal A.; Carey, Ryan M.; Workman, Alan D.; Tong, Charles C.; Kohanski, Michael A.; Palmer, James N.; Adappa, Nithin D.; Newman, Jason G.; Brant, Jason A. (Journal of Neurological Surgery Part B: Skull Base, 2019)
Background Sinonasal adenocarcinoma (SNAC) is a rare malignancy arising from mucus-secreting glandular tissue. Limited large-scale studies are available due to its rarity. We evaluated SNAC in the National Cancer Database (NCDB), a source that affords multi-institutional, population studies of rare cancers and their outcomes.Methods The NCDB was queried for adenocarcinoma in the sinonasal tract. Multivariate analyses were performed to evaluate for factors contributing to overall survival (OS).Results A total of 553 patients were identified. The cohort was composed of 59.3% males. The nasal cavity was the most common primary site, representing 44.1% of cases. About 5.7% of patients presented with nodal disease, while 3.3% had distant metastases. About 40.6% of cases presented with stage IV disease. About 73.5% of patients underwent surgery, 54.2% received radiation therapy, and 27.7% had chemotherapy. Median OS was 71.7 months, while OS at 1, 2, and 5 years was 82, 73.0, and 52%, respectively. On multivariate analysis, advanced age (hazard ratio [HR]: 1.04; 95% confidence interval [CI]: 1.02–1.05), Charlson–Deyo score of 1 (HR: 1.99; 95% CI: 1.20–3.30), advanced tumor grade (HR: 2.73; 95% CI: 1.39–5.34), and advanced tumor stage (HR: 2.71; 95% CI: 1.33–5.50) were associated with worse OS, whereas surgery (HR: 0.34; 95% CI: 0.20–0.60) and radiation therapy (HR: 0.55; 95% CI: 0.33–0.91), but not chemotherapy (HR: 1.16; 95% CI: 0.66–2.05), predicted improved OS.Conclusions SNAC is a rare malignancy with 5-year survival approximating 50%. Surgery and radiation therapy, but not chemotherapy, are associated with improved survival, and likely play a critical role in the interdisciplinary management of SNAC.
Keywords: National Cancer Database; sinonasal adenocarcinoma; skull base; cranial base; nose and paranasal sinuses; outcomes/cost-effectiveness